Comparison of Efficacy of Dipeptidyl Peptidase‐4 Inhibitors and Sodium‐Glucose Co‐Transporter 2 Inhibitors Between Japanese and Non‐Japanese Patients: A Meta‐Analysis - Yuka Ito; Kaori Ambe; Toshiki Hayase; Mayu Kobayashi; Masahiro Tohkin (Wiley, 2020)
We explored efficacy of dipeptidyl peptidase‐4 inhibitors (DPP‐4is) and sodium‐glucose co‐transporter 2 inhibitors (SGLT2is) between Japanese and non‐Japanese patients with type 2 diabetes mellitus by conducting a systematic review and meta‐analysis. A literature search of public databases before May 2017 identified 91 (DPP‐4i) and 63 (SGLT2i) randomized placebo‐controlled trials (> 12‐week treatment). Multivariate meta‐regression analysis identified baseline hemoglobin A1c (HbA1c) levels and placebo responses as covariates affecting efficacy of two agent classes independently of study region (Japanese/non‐Japanese). When accounted for covariates, DPP‐4i caused more pronounced HbA1c reduction in Japanese studies than in non‐Japanese studies by 0.18% difference (P < 0.05) while causing no difference in fasting plasma glucose reduction between regions. On the other hand, when adjusted by baseline HbA1c levels and placebo responses, efficacy of SGLT2i were comparable between regions. The contrasting results for two agent classes indicate that drug efficacy is affected by different pathophysiology at its therapeutic action point.